Effectiveness of sports biomechanics module based on literacy skills to improve student concept understanding - Umar Umar; Alnedral Alnedral; Padli Padli; Pringgo Mardesia (Jurnal Keolahragaan, 2022)
This study aims to determine the results of developing a sports biomechanics module based on literacy skills to improve conceptual understanding and determine how student responses affect student concept understanding. This module was developed using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Before testing, the module must be validated. The results of the material expert validation obtained a score of 4, which was in the excellent category. The media expert validation obtained a score of 4, which was in the excellent category. Moreover, the results of language validation also obtained a score of 4, which means excellent. The results of trials conducted on 90 students showed a positive response where 60% of students stated that this product was good to use. The results of the product effectiveness test were carried out by looking at the effect of the response with the understanding of students' concepts using regression testing. The results of the simple linear regression test showed results of 54.1% on the coefficient of determination which indicated that there was an effect of student responses on understanding the concept. So that the use of this biomechanics module is effective for use in the learning process.